When Intentions Meet Realities: Typology of Contacts across the Finnish-Russian Border - Heikki Eskelinen (European Regional Science Association (ERSA), 2001)
When Intentions Meet Realities: Typology of Contacts across the Finnish-Russian Border Heikki Eskelinen, University of Joensuu, Finland Dmitri Zimine, St. Petersburg Centre for Russian Studies, Russia Cross-border cooperation can be defined as conscious joint activity pursued by local and regional governments with more or less strong support from civil society, and facilitated and constrained by central governments and international organisations. Since about 1990, this phenomenon has also been witnessed across the former Iron Curtain, simultaneously with various forms of cross-border economic transactions and informal contacts. Yet in most cases, cross-border regionalisation has remained rather weak, and it has not met the early ambitious targets of creating a new borderless Europe. Given the background outlined above, the present paper attempts to clarify the interplay of official cooperation and informal cross-border contacts: whether they have developed in accordance - or at least in touch - with each other. For this purpose, a typology of cross-border contacts is created by dividing them into formal v. informal and private profit-oriented (economic) v. public benefit-oriented (political) ones. The basic assertion of the paper is that the lack of regionalisation phenomena across divisive borders may result from that these different forms of cross-border interaction develop independently from each other. The empirical analysis focusses on one border town in the Russian North-West. It attempts to clarify in detail the mechanisms through which various forms of cross-border contacts have influenced developments in it, modifying the transition process at a local level. The observed dynamics of cross?border contacts leads to a conclusion that the four types of cross-border contacts have displayed very different trends in the 1990s, and they have failed to create joint dynamics because of the obstacles imposed by the existing institutional realities on both sides of the border. On this basis, it is asked whether the strengthened informal cross?border networks may well soon begin to exert pressure upon formal public and private institutions with the aim to further develop the formal framework facilitating cross?border contacts.
Keywords: 330